Locating Logical Necessity in Models or the Nature of Situations - Xianrui Liu (Problemos)
Logical necessity is a pivotal notion in accounting for logical consequence, while the source of logical necessity is not widely discussed. In this article I bring to attention one peculiar phenomenon that not only the model-theoretic tradition, but also the essentialist account regarding logical necessity could locate the source of it in logical constants or logical notions. I argue that, under the former tradition, logical constants could be assimilated to restrictions of admissible models, and it is more plausible to locate the source of logical necessity in models; while, under the latter account, and borrowing ideas from the former, we should locate the source of logical necessity in the nature of what models represent, i.e., situations.